Simulasi CFD Pembakaran Non-Premixed Serbuk Biomass Kayu Jati - Tri Istanto; Suyitno Suyitno (Institute of Research and Community Outreach, Petra Christian University, 2005)
Energy crisis in Indonesia for the long time is very dangerous for human live. Therefore, diversifications of the energy resources and the energy conversions are urgently required. One of the sources of energy which is very interesting and very competitive is biomass. The objective of this research is to analyse the combustion characteristics of the Tectona Grandis wood by using CFD (Computational Fluid Dynamics) simulation. The diameter of combusting reactor is 0.5 m and the length is 10 m. The biomass is pulverized and sieved to 40 mesh. Several parameters are varied i.e, wall temperature from 800 K to 1000 K, the mass flow rate of biomass from 0.1 kg/s to 1 kg/s and the moisture content from 0% to 20% d.b. From this model can be simulated combusting gas temperature profile, devolatilization rate, burning rate and concentration of the combusting gas (CO2, H2O and CO). From the simulation can be concluded that higher gas temperature and lower CO pollution can be attained by using higher wall temperature, lower moisture content and lower ratio of air-biomass. The peak temperature of combustion gas can reach 1200K to 1500K. The source of CO pollution is not only from devolatilization process, but also from the reaction between remaining char and H2O. Abstract in Bahasa Indonesia : Krisis energi di Indonesia dalam jangka waktu yang lama sangat berbahaya bagi kehidupan manusia. Oleh karena itu penganeka-ragaman sumber-sumber energi dan metoda untuk mengubahnya menjadi sangat mendesak untuk dilakukan. Salah satu sumber energi yang sangat menarik dan sangat kompetitif adalah biomas. Tujuan dari penelitian ini adalah untuk mengalisis karakteristik pembakaran pada kayu jati dengan menggunakan simulasi CFD. Diameter dari ruang bakar adalah 0,5 m dan panjangnya 10 m. Biomas dibuat serbuk dan diayak sampai ukuran 40 mesh. Beberapa parameter yang divariasikan dalam simulasi yaitu temperatur dinding ruang bakar dari 800 K sampai 1000 K, laju aliran massa biomas dari 0,1 kg/s sampai 1 kg/s dan kadar air dalam biomas dari 0% sampai 20% basis kering. Model ini dapat mensimulasikan profil temperatur gas pembakaran, laju devolatilisasi, laju pembakaran arang dan konsentrasi gas pembakaran (CO2, H2O and CO). Dari hasil simulasi dapat disimpulkan bahwa temperatur gas pembakaran yang tinggi dan polusi CO yang rendah dapat diperoleh dengan menggunakan temperatur dinding lebih tinggi, kadar air lebih rendah dan rasio udara-biomas yang lebih rendah. Temperatur puncak gas pembakaran dapat mencapai 1200K sampai 1500K. Sumber polusi CO tidak hanya berasal dari proses devolatilisasi tetapi juga dari reaksi antara karbon sisa dengan H2O. Kata kunci: CFD, non-premixed, pembakaran, kayu jati.